"We've got a better situation": the life and afterlife of virtual communities in Google Lively. Issue 3 (11th May 2015) - Huvila, Isto
Abstract : Purpose: – The purpose of this paper is to discuss the impact of unsustainable community platforms from community and information sharing perspectives using Google Lively as an example. The aim is to analyse what happens when a community platform is not sustainable and explore the reasons why Lively failed or succeeded as an arena of participation and information sharing. Design/methodology/approach: – The study is based on an ethnographically informed analysis of texts on Google Lively mined from the web and gathered using two small qualitative surveys. Findings: – The findings show that Lively fostered the emergence of several virtual communities that outlived the platform. Shared experience, experience of crisis and a distinct identity appeared to be significant factors that seemed to contribute to the success of analysed Livelian communities. Research limitations/implications: – The study is based on a convenience sample and an analysis of one virtual community platform. Practical implications: – The results inform the development of community strategies for situations when a platform is closing and plans are being made for the sustained existence of the virtual community in new contexts. Originality/value: – This is the first comprehensive study on Google Lively. The findings can be expected to have relevance also in the context of comparable virtual community platforms.